2007
DOI: 10.1634/stemcells.2006-0325
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Stem Cell Lineages in Murine Bone Marrow

Abstract: Mesenchymal stem cells (MSC), a distinct type of adult stem cell, are easy to isolate, culture, and manipulate in ex vivo culture. These cells have great plasticity and potential for therapeutic application, but their properties are poorly understood because of their low frequency and the lack of knowledge on cell surface markers and their location of origin. The present study was designed to address the undefined lineage relationship of hematopoietic and mesenchymal stem cells. Genetically marked, highly puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 53 publications
1
52
0
Order By: Relevance
“…With regard to the phenotype of primary MSCs in murine BM, Koide et al 51 reported that the marker combination PDGFR␣ + Sca-1…”
Section: Prospective Isolation Of Murine Bm-mscs Based On Surface Marmentioning
confidence: 99%
“…With regard to the phenotype of primary MSCs in murine BM, Koide et al 51 reported that the marker combination PDGFR␣ + Sca-1…”
Section: Prospective Isolation Of Murine Bm-mscs Based On Surface Marmentioning
confidence: 99%
“…However, given the heterogeneity of the bone marrow and the multiple molecular markers identified so far, it is unclear whether bone marrow actually contains an endogenous group of skeletal stem cells that can be recruited systemically during bone repair to form cartilage and/or bone. [41][42][43] The difficulty comes from the small percentage of MSCs within the bone marrow and their close association with cells from the hematopoietic lineage. 44 Further in vivo analyses are required to better understand BMSCs' normal physiological functions.…”
Section: Systemic Recruitment Of Cells During Bone Repairmentioning
confidence: 99%
“…Lastly, it has been shown that a subset of CD45(þ) Lin(À) bone marrow cells was able to differentiate in vitro into a variety of cell types, including endothelial cells, osteoblasts, muscle cells, and neural cells [Rogers et al, 2007]. Interestingly, others have failed to confirm that MSCs and HSCs may share a common lineage [Koide et al, 2007]. Further investigations are needed to clarify the discrepancies among the different studies, which nonetheless do raise questions about either the reliability of CD45 as an exclusive hematopoietic cell marker or, rather, the existence of a clear boundary between HSCs and MSCs.…”
Section: Origin Of Bone Marrow Mscs and Char-acterization Of Their Nichementioning
confidence: 99%